Study Of The Surface Integrity Of The Machined Workpiece In The Wedm Of Tungsten Carbide - Mas Ayu, Hassan; Rosdi, Daud; Siti Haryani, Tomadi (2008)

(untitled)
This paper presented a study on the surface integrity of the machined surface of tungsten carbide (WC-15%Co) using wire electro-discharge machining (WEDM). WEDM tests on a WC-15%Co workpiece were conducted on a Sodick WEDM 5-axes series AQ537L, with the pulse duration (ON), pulse interval (OFF), peak current (IP) and servo voltage (SV) varied. The WEDMed surface roughness and thickness of recast layer were examined with a Scanning Electron Microscope XL40. The Full Factorial Design of Experiment (DOE) approach with two-level was used to formulate the experimental layout and to evaluate the effects on two machining responses consisting of surface roughness and thickness of recast layer. It is found that pulse duration has appeared to be the significant effect to both responses. It is also observed that there was almost no presence of microcracks in this study. The recast layer has distinguished microstructure from its parental material which consists of a lot of pockmarks, voids and globules of debris on its surface. Based on the observation done, the WEDM conditions have no effect on the microstructure of the bulk workpiece material. This means that damage caused by WEDM on the WEDMed surface is limited to certain depth only. Overall, the results showed that the thickness of recast layer and surface roughness of machined surface were improved when pulse duration and peak current were set at low values.